A review on biological carbon sequestration - Gayathri, R.; Mahboob, Shahid; Govindarajan, Marimuthu; Al-Ghanim, Khalid; Ahmed, Zubair; Al-Mulhm, Norah; Vodovnik, Maša; Vijayalakshmi, Shankar (Journal of King Saud University - Science, 2022)
Carbon dioxide gas is the key element of the carbon cycle and a major source for photosynthesis, but for the past 150 years, the atmospheric CO2 has been increased drastically from 250 to 418 ppm due to the extreme utilization of fossil fuels. This accelerated release of CO2 acts as a major source for climatic change due to the greenhouse gas effect resulting in global warming and melting of polar ice caps, alteration in biogeochemical cycles, altered rainfall, ocean acidification, eutrophication of lakes, imbalance in the ecological communities and extinction of some species, effects on soil fertility, changes in the metabolism and at the molecular level. Reduce, reuse and recycle strategy can be applied to control elevated CO2 levels by preventing deforestation, using renewable energy as an alternative for fossil fuels and reusing the atmospheric CO2. Carbon capture and storage (CCS), Carbon capture and utilization (CCU) are the two technologies adapted to capture the atmospheric CO2, utilize it, and focus on permanent storage in the geological sites. Captured CO2 is used to produce many value added products such as polymers, biofuels, reactants etc. Plants and microorganisms act as a natural CO2 filter. Several biomolecules such as carbohydrates, proteins, and lipids are produced due to the biological carbon fixation process using photosynthesis. Six different photosynthetic pathways and some non-photosynthetic pathways to fix atmospheric CO2 have been reported in diverse species of plants and microbes such as bacteria, fungi, yeast, algae etc. Algae are the most potent microbe in CO2 utilization and biological carbon fixation compared to other microbes and used widely on a large industrial scale for biofuel production. Algal biofuel production using captured CO2 is the best productive method to recycle and reduce atmospheric CO2.